1995
DOI: 10.1007/bf01946919
|View full text |Cite
|
Sign up to set email alerts
|

Origin and identification of bacteria which produce kairomones in the frass ofAcrolepiopsis assectella (Lep., Hyponomeutoidea)

Abstract: The volatiles used by the parasitoid Diadromus pulchellus to find its host, the leek moth, are produced by the bacteria developing in the frass of the host larvae. The origin and the nature of these bacteria were investigated. Samples were taken from healthy leeks and from infested leeks in the field, as well as from the frass of larvae reared in the laboratory either on the host plant or on an artificial diet. The various species of bacteria identified were cultured in the presence of precursors of leek sulph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Commensal gut microbiota of locusts were previously shown to continually produce aggregation pheromones in frass [13][14][15]. Klebsiella oxytoca and several Bacillus species in the feces of Acrolepiopsis assectella produced kairomones that attract parasitoids [59]. Volatiles in D. valens frass have been illustrated to affect adult beetles' behavior [9,34].…”
Section: Discussionmentioning
confidence: 98%
“…Commensal gut microbiota of locusts were previously shown to continually produce aggregation pheromones in frass [13][14][15]. Klebsiella oxytoca and several Bacillus species in the feces of Acrolepiopsis assectella produced kairomones that attract parasitoids [59]. Volatiles in D. valens frass have been illustrated to affect adult beetles' behavior [9,34].…”
Section: Discussionmentioning
confidence: 98%
“…These authors also suggested that stable fly development depends on a live microbial community in the natural habitat and that fly females are capable of selecting an oviposition site based on the microbially derived stimuli that indicate the suitability of the substrate for larval development. Hymenoptera Thibout et al (1993Thibout et al ( , 1995 have identified sulphur containing volatiles such as alkyl disulphides (dimethyl Table 4 Semiochemically mediated interactions between bacteria and Diptera (Muscidae) P. D. Leroy et al disulphide and dipropyl disulphide) from bacteria (Bacillus sp. and Klebsiella oxytoca) which attract and help the parasitoid Diadromus pulchellus (Hymenoptera: Ichneumonidae) to locate its hosts Acrolepiopsis assectella (Table 5).…”
Section: Muscidaementioning
confidence: 99%
“…This was done by comparing between the responses of C. marginiventris females towards odors from frass derived from Bt maize tissue and responses towards odors from frass derived from conventional maize tissue treated with the broad-spectrum antibiotic tetracycline. Previous studies showed that bacteria present in the gut and frass of insects are responsible for producing volatiles that are attractive to parasitoid females (Auger et al 1990;Thibout et al 1993Thibout et al , 1995, and that lepidopteran gut bacteria are generally susceptible to tetracycline (Visotto et al 2009). Our study is the first to question whether GM crops, including Bt maize, negatively affect chemical communication between foraging parasitoids and their hosts via alteration of host frass, an important source of odors that are useful for locating hosts at short ranges.…”
Section: Introductionmentioning
confidence: 99%